Drought and property prices: Empirical evidence from Iran - Mohammad Reza Farzanegan; Mehdi Feizi; Hassan Gholipour Fereidouni (Philipps-University Marburg, School of Business and Economics, 2019)
This study demonstrates an economic consequence of climate change and water crises in Iran. It examines the effect of drought on housing prices, residential land prices, and housing rents in Iran. Using data from provinces of Iran from 1993 to 2015 and applying static and dynamic panel fixed effects estimators, we find evidence that an increase in the balance of water (reducing the severity of drought) within provinces has a positive effect on property prices. Our results have important implications for Iranian policymakers and property investors.
Keywords: R21; R31; Q54; 330; Drought; Water Crisis; Property Prices; Housing; Iran